The topographic-based v s30 model of the Opak River basin Yogyakarta - Nugroho Budi Wibowo; Teuku Faisal Fathani; Subagyo Pramumijoyo; Gayatri Indah Marliyani (Geoenvironmental Disasters)
Abstract Background Accurate v s30 values are crucial for earthquake hazard assessment. The ongoing development of the v s30 Model aims to yield the most precise representation of field conditions. Geological characteristics such as elevation, slope, and land development parameters are crucial. The Opak River area is located in the boundary of Young Merapi Deposit Group and the Southern Mountains litological units. This area has a history of seismic activity, notably the 2006 Yogyakarta earthquake. Purpose The research aims to develop a v s30 model based on geological and topographic parameters. Methods The v s30 reference data relies on v s30 microtremor data, validated through MASW, N-SPT, and seismic borehole data. Validation v s30 microtremor data with MASW yields a correlation coefficient of 0.98, while the correlation coefficient for the v s30 microtremor profile with N-SPT ranges from 0.68 to 0.98. Both v s30 microtremor and seismic borehole data categorize sites similarly. Results The v s30 model's development employs multiple regression with topographic parameters (elevation, slope, Terrain Ruggness Index and Topographic Position Index). The modeling process yields four v s30 equation models with multiple regression coefficients ranging from 0.82 to 0.99. Conclusion This model is expected to be applicable to seismic vulnerability models for earthquake preparedness and civil engineering practices.